New data on distribution and taxonomy of the genus Suncus (Mammalia: Soricidae) in Iran; molecular evidence - Ahmad Mahmoudi; Jamshid Darvish; Abdulwahed Pehpuri; S. Saeidzadeh (Iranian Journal of Animal Biosystematics, 2017)
We studied 1140 base pairs of mitochondrial cytochrome b gene of small shrews from Iran. Using previous published data for Suncus Ehrenberg 1832, phylogenetic trees showed affiliation of Iranian haplotypes to Madagascan Pgymy Shrew, Suncus madagascariensis that is the first report of the species for Iranian plateau, questioning the presence of Suncus etruscus for the country. Kimura 2 parameter genetic divergence of 5.4% between the two nominative geographic clades, etruscus and madagascariensis (the Western and Eastern) is located beyond of intraspecific divergence for mammalian cytochrome b (2.4%). This finding reflects the importance of molecular data to discriminate groups, when traditional approaches are not adequate, as well as it sheds more light on the current geographic range of small shrews.